Aspectos discursivos da constituição da autoria em resenhas acadêmicas - Lima, Carla da Silva (2008)
This paper has as its main goal to characterize, from a discursive perspective, some aspects of the process of authorship constitution in academic reviews published in scientific publications in the Linguistics field (QUALIS A), specifically the published reviews in the journal DELTA, in its digital version. To accomplish this, we began the analysis work identifying the discursive positions which pointed to different ways of insertion of the subject while authorsubject within the scenic picture academic review. We assumed that the authorship is conditioned, regulated by the enunciation scene, particularly by the discourse scenic picture, as the subject inserts itself in the enclosing academic scene, but it only constitutes itself in the authorfunction within a generic scene. To proceed to the analysis of the 20 reviews that compound the corpus of the research, we took as basis the analyticaltheoretical device of the French line Discourse Analysis, considering as theoretical reference to the authorship matter Foucalt s (1969, 1971) and Possenti s (2001, 2002) reflexions and as central axis of the discussions the scene notion of enunciation formulated by Maingueneau (1987, 2006), particularly what he defines as discourse scenic picture the enclosing scene and the generic scene as reference to the analysis of the class category and its coercions over the authorship constitution processes. The data analyzed indicate that the subject of the discourse inserts itself in different ways in the enclosing academic scene, and these insertions produce different authorship effects, depending on the position that the reviewer assumes towards the Other, such position materializes itself in the texts, among other ways, on the demonstrated marks of heterogeneity.